Public Debt and Economic Growth in Nepal - Shrestha, Pratibha (Khwopa Journal, 2023)
In case of increasing both internal and external debts in Nepal, this paper investigates the impact of internal and external outstanding debt along with gross fixed capital formation, broad money supply, total trade and national consumer price index on real GDP of Nepal for the period 1975 to 2021. The study applied domestic data sets with ordinary least square series. Unit root and cointegration tests are carried out. The cointegration results confirm long run relationship. The empirical results show that both the internal and external outstanding debts are contributing to real GDP in Nepal. The results are supported by econometric diagnostic tests. Based on the results, the paper recommends that taking public debt and investing in public sector is beneficial for real sector output in Nepal.